Assessing changes in static and dynamic postural stability in youth football players following the FIFA 11+ injury prevention program - Bahari Fard, R.; Ebrahimi Atri, A.; Khoshraftar Yazdi, N. K.; Shahtahmassebi, B. (Science & Sports, 2022)
Objective To examine the effect of FIFA 11+ warm-up program on static and dynamic postural stability in football players. Equipment and methods: Thirty young male football players (mean ± SD; age: 14.96 ± 0.76 years were recruited and divided into two groups (FIFA 11+ exercise group, n = 15 and control group, n = 15). The exercise group performed the FIFA 11+ injury prevention exercises as part of their warm-up and the control group continued their traditional warm up routines. The FIFA 11+ exercises were performed three times a week, for eight weeks. A single leg test with eyes closed, on a force platform, was used to measure static postural stability measurement, and time to stability after single leg drop-landing test was used for dynamic postural stability measurement. Results The repeated measures (Anova) showed that the experimental group performed significantly better (adjusted mean difference [95% CI] or percentage %) in static postural stability (center of pressure displacement in the anterior-posterior direction [0.03 (95% CI 0.003 to 0.06), 8.56%] and medial-lateral [0.05 (95% CI 0.02 to 0.08), 9.19%]), and in dynamic postural stability (time to stability in the anterior-posterior direction [0.64 (95% CI 0.09 to 1.2), 15.82%] and medial-lateral [0.6 (95% CI 0.01 to 1.2), 18.92%]), compared with the control group. In conclusion, The FIFA 11+ injury prevention program may improve static and dynamic postural stability.